Effect of Heat Treatments on the Microstructure and Wear Behaviour of A Selective Laser Melted Maraging Steel - Özer, Gökhan; Khan, Hamaid Mahmood; Tarakçı, Gürkan; Yılmaz, Mustafa Safa; Yaman, Paşa; Karabeyoğlu, Sencer Süreyya; Kısasöz, Alptekin (SAGE, 2022)
This study applied classical and intercritical heat treatments to maraging steel (MS1) samples produced with standard additive manufacturing (AM) production parameters. The effects of heat treatment parameters on the microstructure-phase changes of the material were investigated by optical microscope (OM), scanning electron microscope (SEM), Electron Dispersion Spectroscopy (EDX), and X-ray diffraction analysis (XRD) techniques. Likewise, microhardness and dry sliding wear tests were performed to determine the relationship of heat treatment parameters (especially intercritical heat treatment) to the mechanical properties and wear of the material. The results reveal that the intercritical heat treatment is exciting for the AM/MS1 material.
Keywords: Direct Metal Laser Sintering (SLM); Maraging Steel (MS1); Wear Properties; Intercritical Heat Treatment; Additive Manufacturing